Calculation of gini and theil inequality coefficients for Irish household incomes in 1973 and 1980 - Murphy, D.C. (Economic & Social Studies, 1985)
The exact values of Gini and Theil inequality coefficients calculated on the basis of discrete data are provided for direct, gross, disposable and final (i.e., after all taxes and State benefits) Irish household incomes in 1973 and 1980. These exact values are used to quantify the errors inherent in the grouped data approximations customarily used in most analyses. It is shown that quantile income classifications in general offer the most consistent approximation basis. A procedure is presented for selecting income ranges to improve the precision of grouped data approximations. Exact Gini and Theil coefficients for direct and final income are also provided for a wide range of different types of households in 1973 and 1980.
Keywords: Inequality coefficients; Household income - Ireland